Inhibitory potential of Gossypium arboreum leaf extracts on diabetes key enzymes, α-amylase and α-glucosidase - Mutiu Idowu Kazeem; Stella Gbemisola Abimbola; Anofi Omotayo Tom Ashafa (Bangladesh Pharmacological Society, 2013)
One of the antidiabetic therapeutic approaches is the reduction in gastrointestinal glucose production and absorption by inhibiting carbohydrate hydrolyzing enzymes such as α-amylase and α-glucosidase. This present study evaluated the α-amylase and α-glucosidase inhibitory potential of the aqueous, ethanolic and acetone leaf extracts of Gossypium arboreum and to further determine the mode of inhibition of the enzymes using kinetic analysis. The aqueous and acetone extract exhibited potent α-amylase and α-glucosidase inhibitory activity with IC50 value of 10.10 mg/mL and 2.75 mg/mL respectively. These extracts are likely to contain non-competitive inhibitors of both enzymes with reduced Vmax values. The extracts were also found to contain phytochemicals such as tannins and steroids which may be responsible for the inhibitory effect. The results show that the aqueous and acetone extracts of G. arboreum leaf inhibited both α-amylase and α-glucosidase at relatively low concentrations and this could be the reason why the species is employed in the management of blood sugar related disorders by reasonable populations in Nigeria.